The Effect Of Alloying Elements On Wear Behaviour Of Ni-Al [TA483. I98 2004 f rb] [Microfiche 7664]. - Ishak, Mohamad Izha (2004)
Considerable amount of research has been performed on nickel aluminide (NiAl) over the last decade, with an exponential increase in effort occurring over the last few years.